Enhancing the sweetening power of lactose by enzymatic modification in the reformulation of dairy products. (29th January 2020) - Luzzi, Giuseppina; Steffens, Marco; Clawin‐Rädecker, Ingrid; Hoffmann, Wolfgang; Franz, Charles M A P; Fritsche, Jan; Lorenzen, Peter Chr
Abstract : Lactose solutions of up to 50% ( w / v ) were incubated with lactases and glucose isomerases for subsequent implementation in dairy product samples to enhance sweetness. A degree of hydrolysis of >90% and of isomerisation of 50% were attainable. The sensory sweetening power of lactose in solutions of up to 50% ( w / v ) can be enhanced 2–3 times. Based on sensory experiments, application of this bi‐enzymatic system in yoghurt and pudding samples allowed for a 10–20% ( w / w ) reduction in the total sugar content, whilst retaining equal sweetness. The growth of yoghurt starter cultures was not affected, yet furosine formation more than doubled in high heated, enzyme‐modified milk.